King of capitalism Thomas Watson Sr. & the building of IBM - Evans, Guy; British Broadcasting Company (Australia : BBC, 2003)
A profile of Thomas Watson Sr., who started as a door-to-door salesman to eventually build the global IBM network. The complexities of Thomas Watson's character is explored through archival materials, stills, home movies and interviews with family and business colleagues. His dealings with the Nazis is discussed and the question of moral responsibility of companies is highlighted
Title from title screen
Executive producer, Adam Bullmore ; editor, Kieran Smyth
Narrator: Jack Darenport
DVD format
Keywords: Watson, Thomas John, -- 1874-1956; International Business Machines Corporation; War -- Economic aspects; Corporate culture -- United States; Capitalism -- United States